Pengelolaan Limbah Plastik menjadi Ecobrick Sebagai Upaya Kolaborasi Mahasiswa KKN UIN Walisongo dengan SDN 2 Rowosari dalam Membangun Taman Ecobrick - Sri Wahyuningsih; Lintang Arjunil Wafa; Mutiara Zaskia; Zulfa Rahayuning Fadhilah; Rizqi Amalia; Zufar Nabiel Darell Althaf (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This study examines the management of plastic waste into ecobricks through the collaboration of UIN Walisongo Real Work Lecture (KKN) students with SDN 2 Rowosari. The purpose of this study is to describe the process of managing plastic waste into ecobricks and analyze the impact of collaboration on environmental awareness at SDN 2 Rowosari. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that the process of managing plastic waste into ecobricks involves the stages of collecting, washing, drying, and packaging plastic in bottles. The collaboration between KKN students and SDN 2 Rowosari proved effective in increasing the environmental awareness of students and teachers, as well as encouraging active participation in plastic waste management. The development of the Ecobrick Garden as a result of this collaboration is expected to be an innovative and sustainable model of environmental learning.